THE IMPEMENTATION OF SCIENTIFIC WITH KONKRET MEDIA TO IMPROVE Â MATHEMATIC LEARNING AT THE SECOUND GRADE STUDENTS OF SDN 1 KUWARASAN IN THE ACADEMIC YEAR OF 2014/2015 - Betari, Sinta Aprilia (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Impementation of Scientific with Konkret Media to Improve Mathematic Learning at the Secound Grade Students of SDN 1 Kuwarasan in The Academic Year Of 2014/2015. The objectives of this study are: 1) to describe the steps of application of the scientific approach with concrete object media, (2) improve the learning of mathematics about the division of natural numbers in the application of scientific approach with concrete object media at the second grade students of SDN 1 Kuwarasan in the academic year of 2014/2015, and (3) describe the constraints and solutions. The subjects were second grade students of SDN 1 Kuwarasan totaling 40 students. The conclusion of this study is the application of scientific approach with concrete object media can improve Mathematics learning about the division of natural numbers at the second grade students of SDN 1 Kuwarasan in the academic year of 2014/2015. Keywords: Scientific Approach, Concrete Media, Learning, Mathematics